Administration of Bifidobacterium bifidum BGN4 and Bifidobacterium longum BORI Improves Cognitive and Memory Function in the Mouse Model of Alzheimer’s Disease - Kim, Hongwon; Kim, Sumin; Park, Sang-jun; Park, Gwoncheol; Shin, Hakdong; Park, Myeong Soo; Kim, Jongpil (Frontiers in Aging Neuroscience, 2021)
Recent evidence indicates that gut microbiota could interact with the central nervous system and affect brain function, including cognition and memory. In this study, we investigated whether Bifidobacterium bifidum BGN4 (B. bifidum BGN4) and Bifidobacterium longum BORI (B. longum BORI) alleviated the pathological features in a mouse model of Alzheimer’s disease (AD). Administration of B. bifidum BGN4 and B. longum BORI effectively suppressed amyloidosis and apoptotic processes and improved synaptic plasticity by ameliorating the neuroinflammatory response and BDNF expression. Moreover, behavioral tests indicated that B. bifidum BGN4 and B. longum BORI attenuated the cognitive and memory disability of AD mice. Taken together, the present study highlights the therapeutic potential of B. bifidum BGN4 and B. longum BORI for suppressing the pathological features of AD.